Βιβλιοκριτικό δοκίμιο:G. STATHIS, Introduction to Kalophony, the Byzantine Ars Nova; The Anagrammatismoi and Mathēmata of Byzantine Chant; translated and revised by K. Terzopoulos; Studies in Eastern Orthodoxy 1; Peter Lang (Bern 2014); Pages 332. - ΧΑΛΔΑΙΑΚΗΣ, Αχιλλεύς (Byzantina Symmeikta, 2016)
Βιβλιοκριτικό δοκίμιο: G. STATHIS, Introduction to Kalophony, the Byzantine Ars Nova; The Anagrammatismoi and Mathēmata of Byzantine Chant; translated and revised by Konstantinos Terzopoulos; Studies in Eastern Orthodoxy 1; Peter Lang (Bern 2014); Pages 332.